Tuberculous Osteomyelitis of the Scapular Spine Revealing HIV-1 Infection - Khaoula Idsaid; Malika Idalene; Khadija Danaoui; Wiam Ait Driss; Rania Elfargani; Nabila Soraa; Noura Tassi (Tropical Medicine and Infectious Disease)
Tuberculosis is no longer confined to developing nations; it persists as a significant contributor to illness and death on a global scale. The subtle clinical manifestation and association with human immunodeficiency virus infection poses obstacles for early diagnosis and management. Tuberculosis manifesting at extrapulmonary sites is relatively rare. We herein present the case of a 26-year-old patient from Cameroon with a history of pleuropulmonary tuberculosis treated in 2008, who had been taking pre-exposure prophylaxis (PrEP). The patient presented with right shoulder pain of an inflammatory type. The case was diagnosed as tuberculous osteomyelitis of the scapular spine, complicated by a deltoid abscess. Diagnosis was confirmed using computed tomography and the MTB/RIF GeneXpert test on the abscess puncture. This rare form of tuberculosis with an exceptional site revealed a HIV infection with profound immunosuppression. The patient was initiated on anti-tubercular treatment according to Moroccan recommendations.